2018
DOI: 10.1093/occmed/kqy042
|View full text |Cite
|
Sign up to set email alerts
|

Health survey of employees regularly using 3D printers

Abstract: Our finding of frequently reported respiratory symptoms suggests a need for additional studies on exposed workers in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 7 publications
0
52
1
Order By: Relevance
“…Ultrafine particles can penetrate deeper into the respiratory system and might be harder to clear from the body 19 . In a study with employees regularly using 3D printers 59% have reported respiratory symptoms 20 4 , 10 , 13 . Furthermore, new filaments, which are provided with additives such as metal or wood, are constantly being launched to the market.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafine particles can penetrate deeper into the respiratory system and might be harder to clear from the body 19 . In a study with employees regularly using 3D printers 59% have reported respiratory symptoms 20 4 , 10 , 13 . Furthermore, new filaments, which are provided with additives such as metal or wood, are constantly being launched to the market.…”
Section: Introductionmentioning
confidence: 99%
“…Along with increased use of 3D printing, environmental issues related to 3D printing should be scrutinized. Ultrafine particles and volatile organic compounds emitted during the 3D printing process may cause occupational health issues, such as an increased risk of respiratory disease and cancer (58)(59)(60). Another environmental issue stems from the fact that 3D printing materials cannot be recycled in most cases (22,58).…”
Section: Unresolved Issuesmentioning
confidence: 99%
“…Chan et al [101] conducted a small-scale survey of 46 occupational users of FFF 3D printers in 17 different companies, in order to identify potential correlations between 3D printing and the emergence of adverse health effects. 59% of participants reported displaying respiratory symptoms at least once per week in the previous year.…”
Section: Health Issues Connected With Fff 3d Printer Usementioning
confidence: 99%
“…It should be mentioned that more than half of the participants (52%) reported not using any form of personal protective equipment (PPE). The authors suggested that further studies should be undertaken to provide further understanding on the risks presented for workers [101]. Gümperlein et al [102] investigated the acute effects of desktop 3D printer emissions on 26 human volunteers.…”
Section: Health Issues Connected With Fff 3d Printer Usementioning
confidence: 99%